Pre-consumption textile waste management in the clothing industry in Teresina/PI - Albuquerque, Simone Ferreira de; Santos, Maria do Socorro Ferreira dos; Moita Neto, José Machado (Sustainability in Debate, 2021)
The garment industry stands out as the second-largest employer in the manufacturing industry, but it is singled out for environmentally and socially unsustainable practices. In this study, managers of ten companies in Teresina (Piauí State, Brazil) were interviewed to investigate textile waste management methods and instruments and the difficulties and challenges found in management. Methodologically, it was used bibliographical, exploratory, documental and case study research. The research instruments were the questionnaire, direct observation and interview. Data were assessed through content analysis. The results show that part of the production-related waste is donated to manufacture rugs and fuxico, discarded for everyday collection. The conclusion we came across is that the clothing industry in Teresina lacks better management of its production process to generate less waste. When it is not possible to reuse it, dispose of it properly.